837. Contamination of Hospital Drains by Carbapenemase-Producing Enterobacterales (CPE) in Ontario, Canada. (31st December 2020) - Jamal, Alainna J; Mataseje, Laura; Brown, Kevin; Katz, Kevin; Johnstone, Jennie; Muller, Matthew; Allen, Vanessa; Borgia, Sergio; Boyd, David; Ciccotelli, William; Delibasic, Kornelija; Fisman, David; et al.
Abstract: Background: The hospital water environment is a CPE reservoir, and transmission of CPE from drains to patients is a risk. Methods: We cultured sink and shower drains in patient rooms and communal shower rooms that were exposed to inpatients with CPE colonization/infection from October 2007 to December 2017 at 10 hospitals. We compared patient room drain CPE to prior room occupant CPE using Illumina and MinION whole-genome sequencing. Results: Three-hundred and ten inpatients exposed 1, 209 drains, of which 53 (4%) yielded 62 CPE isolates at 7 (70%) hospitals. Compared to room occupant CPE isolates, drain CPE isolates were more likely Enterobacter spp. (6, 10% vs. 25, 51%, p< 0.0001) or KPC-producers (9, 15% vs. 23, 47%, p=0.0002). Of the 49 CPE isolates in patient room drains, 4 (8%) were linked to a prior room occupant (Table), 24 (49%) had the same carbapenemase as a prior room occupant but isolates/carbapenemase gene-containing plasmids that were unrelated, and 21 (43%) did not share a carbapenemase with a prior room occupant. The 4 drains linked to prior room occupants were likely contaminated by these room occupants, who were CPE-colonized prior to drain exposure. Despite few links between drain and room occupant CPE, there were 10 isolates harbouring related bla NDM-1 -containing IncHI2A/HI2-type plasmids in 8 rooms on two units at one hospital. Nine of these were Enterobacter hormaechei ST66 isolates that were 0 to 6 SNVs apart and one was a Klebsiella oxytoca STnovel isolate. Table. Four patient room drain CPE isolates (D1b, D4, D5, D12) and isolates from prior room occupants that they were related to by whole-genome sequencing. Conclusion: It was uncommon for drain CPE to be linked to prior patient exposure. This suggests contamination of most drains by undetected colonized patients and a need for more aggressive patient screening in our hospitals. This may also suggest retrograde (drain-to-drain) transmission, especially considering the 10 isolate drain cluster at one hospital. Reasons for the preponderance of Enterobacter spp. in drains requires further study. Disclosures: Allison McGeer, MD, FRCPC, GlaxoSmithKline (Advisor or Review Panel member, Research Grant or Support)Merck (Advisor or Review Panel member, Research Grant or Support)Pfizer (Research Grant or Support)